JEJAK BUDAYA PENUTUR AUSTRONESIA PADA SITUS KAMPUNG FORIR, FAKFAK (The Last Vestiges of The Austronesian Culture in Kampung Forir Site, Fakfak) - Sukandar, Sri Chiirullia (BALAI ARKEOLOGI PAPUA, 2015)
Research on Sosoraweru cave site and Kampung Forir site, shows a number of issues Austronesian context. There are two issue to be discussed in this article, namely: (1) Traces of Austronesian speakers in Kampung Furir; (2) Function Sosoraweru cave site in the past. To explore both of these issues used the method of observation, excavation, and literature and analyzed based on contextual analysis. The baseline data obtained and analyzed in the form of artifacts and ekofak the influence of Austronesian culture in the southwestern coast of Papua. Based on the data and the context concluded that traces the influence of Austronesian in Sosoraweru cave include: red slip pottery fragments, the system of burial niches and frescoes which show the influence of Austronesian cultures. In addition, based on the context of the locus is known that the Sosoraweru cave site and Kampung Forir site serve as a residential in the past.AbstrakPenelitian di Situs Kampung Forir dan Gua Sosoraweru memperlihatkan sejumlah konteks isu Austronesia. Ada dua masalah yang akan dibahas dalam artikel ini, yaitu: (1) Jejak penutur Austronesia di Kampung Furir; (2) Fungsi situs Gua Sosoraweru di masa lalu. Untuk mendalami kedua masalah tersebut, digunakan metode observasi, ekskavasi, dan studi pustaka. Data-data pokok yang diperoleh dianalisis berdasarkan analisis kontekstual, berupa artefak dan ekofak untuk melihat adanya pengaruh budaya Austronesia di kawasan pesisir baratdaya Papua. Berdasarkan data dan konteksnya disimpulkan bahwa jejak pengaruh Austronesia di Gua Sosoraweru meliputi: fragmen gerabah berslip merah, sistem penguburan ceruk dan lukisan dinding yang menunjukkan adanya pengaruh budaya Austronesia. Selain itu, berdasarkan konteks lokus temuan diketahui bahwa Gua Sosoraweru dan kawasan Kampung Forir berfungsi sebagai hunian di masa lalu